The History of Don Quixote, Volume 2, Part 40 - Cervantes Saavedra, Miguel de, 1547-1616; Doré, Gustave, 1832-1883; Ormsby, John, 1829-1895 (Salt Lake City, UT : Project Gutenberg, 2004)
"The History of Don Quixote, Volume 2, Part 40" by Miguel de Cervantes Saavedra is a section of a novel originally published in two parts in 1605 and 1615. This installment continues the adventures of the delusional knight-errant Don Quixote and his practical squire Sancho Panza. As the pair journey through Spain, their contrasting worldviews create both comedy and drama, with Don Quixote's chivalric fantasies clashing against everyday reality while Sancho provides earthy wisdom and commentary on their misadventures. (This is an automatically generated summary.)
HTML file
Wikipedia page about this book: https://en.wikipedia.org/wiki/Don_Quixote
Release date is 2004-06-01
Produced by David Widger
Keywords: Spain -- Social life and customs -- 16th century -- Fiction; Knights and knighthood -- Spain -- Fiction; Picaresque literature; Romances